CORN PROCESSING WITH ULVA LACTUCA SEAWEED FORTIFICATION AS HEALTHY SNACK - Lasindrang, Musrowati; Pustikaningsih, Adeng; Samlawi, Ahmad; Marjuki; Setyawami; Sunaryo, (Journal Humanitarian Responsibilities, Education & Sport Sciences (JHRESS), 2025)
The implementation of the community empowerment program through corn processing with seaweed fortification in 2024 was carried out in Pacarejo Kapanewon Semanu village, Gunungkidul Regency, Yogyakarta. The purpose of this program is to increase community income through Small and Medium Enterprises, increase local creativity and innovation that can be used as a typical product of the Gunungkidul region and increase the selling value of Corn commodities in Pacarejo Village. The solution that can be done is through processing corn raw materials into delicious, nutritious and preferred products and can become regional specialty products that can compete with other regions. The methods used in this program are counseling and training methods. This program collaborates with the PKK Prima Melati group in Pacarejo Village as a partner in the processing of corn into corn sticks and Pacarejo Village as a partner in the marketing process of snack products. The flow of activities includes counseling on how to make corn sticks and entrepreneurial techniques, training in making sticks, as well as packaging and marketing of processed corn products.